DAMPAK URBANISASI BAGI PERKEMBANGAN KOTA DI INDONESIA - Fitri Ramdhani Harahap (Society, 2013)
This paper discusses the impact of urbanization posed by the rapidly developing city. Urbanization is the result of urban development and economic which ultimately affect the dynamics of the city, especially in contact with the city's ability as an attraction for people to work and live. The impact of urban development is first, physical: land vs land up green, the distribution of urban facilities, transportation networks, patterns of movement to the city center, the development of land use, environmental issues, and slums. Second, socially; unemployment, poverty, and criminalitas.